A formação extemporânea do leitor de literatura: o romance Éramos Seis e o trabalho proletário - Rosa Maria Saraiva Lorenzin (2021)
This present work proposes the development of a teaching project for working students of Educação de Jovens e Adultos – EJA – at the Padre Marzano Matias Municipal School. Most of these students are averse to literary reading and have never done the full reading of a book, therefore the project is based on the reading of the novel Éramos seis, which presents proletarian characters in the story like most of these EJA students, leading them to realize a meaningful reading, of interest to them, which generates the pleasure of reading and contributes to the extemporaneous training of literature readers, in a phase in which literary literacy should have already been completed in the early years of basic education, hence the use of the term “untimely”, outside the proper tense for literacy. The teaching project will have as methodology the application of a didactic sequence and workshops with activities related to the situation of the Brazilian proletariat and the labor laws of the time in which the narrative of Éramos seis (1910s to 1940s) and the current labor laws. The initial objective of the project was to be applied in the classroom during the research period of the Masters, however due to the Covid-19 pandemic and the consequent suspension of classes for an indefinite period, there was a need to change the project, which passed to be a teaching proposal. Therefore, the results of research about the profile of the working student, the profile of the student reader of the EJA and the verification of literary literacy will not be known in this work, but they remain as a proposal for a new research to be carried out a posteriori.